Hungarian Monitoring, 13 May 1990 . [Magyar rádiófigyelő], 1990. május 13 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - The Democratic Alliance of Hungarians in Romania (RMDSZ) supports postponing the upcoming elections in Romania - GDR plans for the withdrawal of Soviet troops - The relation between the USSR and the Baltic states - Local municipality elections in the GDR - Wałęsa's official declaration of war against the Polish government Domestic Affairs: - Lajos Für on Hungarian-Romanian relations - László Tőkés's ordination as bishop - The hydroelectric power plant construction continues in Gabčíkovo-Nagymaros - Honorary doctorate for Árpád Göncz Külpolitika: - Az RMDSZ elhalasztaná a romániai választásokat - NDK elképzelések a szovjet csapatok kivonulásáról - A Szovjetunió és a balti államok viszonya - Helyhatósági választások az NDK-ban - Walesa hivatalos hadüzenete a lengyel kormány ellen Belpolitika: - Für Lajos a magyar-román viszonyról - Tőkés László püspökké avatása - Bősnél tovább épül az erőmű - Göncz Árpádot díszdoktorrá avatták